2019
DOI: 10.1002/hpja.273
|View full text |Cite
|
Sign up to set email alerts
|

Teacher perceptions of sun protection practices in the secondary school setting: Barriers, enablers and recommendations for future

Abstract: Objective: This qualitative study aimed to explore sun protection barriers and enablers in secondary schools in Victoria.Methods: Five focus groups were conducted with nominated Health or Physical Education (PE) Coordinators (or other staff representatives) from schools in metropolitan and regional Victoria. Discussions were audio-recorded, transcribed and coded thematically.Results: Participants identified the need for regulatory influences that included minimum standards for sun protection policy, training a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Demographic factors were more strongly associated with use of sun protective clothing and accessories than with shade cover. This may be because social norms surrounding clothing and accessories relate to fashion and social identity (Potente et al, 2011), while there may be weaker social norms for avoidance of shade which relate to pursuit of a suntan (Dobbinson et al, 2014; Nicholson et al, 2020). Shade use is also dependent on thermal comfort (as described in a socioecological model) and shade availability (Buller et al, 2016; Buller et al, 2017; Dobbinson et al, 2014; Nicholson et al, 2020; Potente et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Demographic factors were more strongly associated with use of sun protective clothing and accessories than with shade cover. This may be because social norms surrounding clothing and accessories relate to fashion and social identity (Potente et al, 2011), while there may be weaker social norms for avoidance of shade which relate to pursuit of a suntan (Dobbinson et al, 2014; Nicholson et al, 2020). Shade use is also dependent on thermal comfort (as described in a socioecological model) and shade availability (Buller et al, 2016; Buller et al, 2017; Dobbinson et al, 2014; Nicholson et al, 2020; Potente et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Educating preservice teachers (PSTs) while at university before they enter schools could be a potential opportunity to improve schools' approaches to sun protection across Australia by facilitating classroom teaching on the UV Index and modelling positive sun safe behaviours to students. 14,15 Anecdotal evidence from one previous study (n = 30) suggests that secondary 1 PST's knowledge about the UV Index is low. 16 However, primary 2 PST's current level of understanding of UV radiation and effective sun protective measures to protect themselves and young children is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PSTs reported no issue with wearing wide‐brimmed hats, long sleeves and sunscreen in school settings and all agreed that it was important that teachers model effective sun protection behaviours to their students. Teachers modelling sun safe behaviours has been shown to positively affect students' sun protection behaviours 33 . Many reported that this was the primary reason for wearing sun protection while in primary schools, rather than being conscious of reducing their own skin cancer risks.…”
Section: Discussionmentioning
confidence: 99%